О чем в тиши ночей... - Танеев Сергей Иванович (Вокальные ансамбли, 1966)
Экземпляры: ИСК (20250610) / Инвентарный номер: н10874 / Сис.шифр: 85.942(2) / Авт.знак: Т 18 / ГРНТИ: 18 / ББК: 85.942(2=411.2)